Eastern Equine Encephalomyelitis in Michigan: Historical Review of Equine, Human, and Wildlife Involvement, Epidemiology, Vector Associations, and Factors Contributing to Endemicity. Issue 1 (4th November 2021) - Stobierski, Mary Grace; Signs, Kimberly; Dinh, Emily; Cooley, Thomas M; Melotti, Julie; Schalow, Michele; Patterson, Jon S; Bolin, Steven R; Walker, Edward D
Abstract: Eastern equine encephalomyelitis (EEE) is a mosquito-borne viral disease that is an emerging public health concern in the state of Michigan. Although Michigan has one of the highest incidence rates of EEE in the United States, much of the information known about cases in humans, equines, and other animals residing in Michigan is unpublished. This article summarizes such information and explores spatial trends in the historic distribution of EEE in Michigan. Outbreaks in Michigan have occurred over an 80-yr interval, involving only horses in 1942–1943 and 1973–1976, and then episodically from 1980 to 2020, and involving horses, humans, and wild and domestic animals. An estimated 1, 036 equine cases (confirmed and suspected) and 36 confirmed human cases have occurred, including 10 in 2019 (6 deaths) and 4 in 2020 (2 deaths). Human cases ranged in age from 1 to 81 yr; 70% were male, and fatality rate of 34.3%. Equine and human cases occurred from July to October, peaked in August, and cluster in space in southwestern and southeastern lower Michigan. Cases occurred in glacial outwash and ice-contact landscapes in glacial interlobate zones. EEE virus (EEEV) was recovered from Culiseta melanura, Coquillettidia perturbans, five species of Aedes, and other mosquito species near horse and human case sites. Virus isolations or presence of neutralizing antibodies in several passerine species of birds suggest broad EEEV–bird associations. White-tailed deer and other wildlife were also affected. Geographic spread to northern areas of the state suggests expansion of this disease system into new and unsuspected foci.